(untitled) (Global Journal of Human-Social Science, 2023)
In February 2022 Russia invaded Ukraine and this act represents a turning point in the world order because it was a step toward the expansionism of Putin s Eurasian Order to challenge the hegemony of the Liberal Order ruled by the United States of America The so-called special military operation aims not only to force Ukraine to reject any approach to Western Europe namely to NATO and European Union but also to fight against American hegemony and to replace the present world order with a new model in a conjuncture when China defends an alleged post-hegemonic world and uses both its sharp power and its wolf warrior strategy to reach it This fact explains China s position toward the war in Ukraine because despite its appeals to peace China never refers to the conflict as a war or an invasion Moreover China has opposed European and North American sanctions on Russia and even saying that Beijing does not provide weapons for the Russian army Xi Jinping refuses to break its no-limits partnership with Russia This chapter proves that this fight against American hegemony represents a strategy to change the world order but not with a post-hegemonic goal In the first moment revisiting the Cold War bipolar order and in the second phase towards a multi-order world also involving a religious dimension